Horizontal transfer of the msp130 gene supported the evolution of metazoan biomineralization. Issue 3 (15th April 2014) - Ettensohn, Charles A.
SUMMARY It is widely accepted that biomineralized structures appeared independently in many metazoan clades during the Cambrian. How this occurred, and whether it involved the parallel co‐option of a common set of biochemical and developmental pathways (i.e., a shared biomineralization "toolkit"), are questions that remain unanswered. Here, I provide evidence that horizontal gene transfer supported the evolution of biomineralization in some metazoans. I show that Msp130 proteins, first described as proteins expressed selectively by the biomineral‐forming primary mesenchyme cells of the sea urchin embryo, have a much wider taxonomic distribution than was previously appreciated. Msp130 proteins are present in several invertebrate deuterostomes and in one protostome clade (molluscs). Surprisingly, closely related proteins are also present in many bacteria and several algae, and I propose that msp130 genes were introduced into metazoan lineages via multiple, independent horizontal gene transfer events. Phylogenetic analysis shows that the introduction of an ancestral msp130 gene occurred in the sea urchin lineage more than 250 million years ago and that msp130 genes underwent independent, parallel duplications in each of the metazoan phyla in which these genes are found.